The historical research into school practice. Presentation - da Silva V.L.G.* (2020)
© 2020 eum (Edizioni Università di Macerata, Italy).This article is an introduction to a collection of papers that present new sources for the study of school and educational practices, such as school writings, teaching instruments, photographs, personal testimonies or teaching material catalogues. The key aspects of daily classroom activities are highlighted through the study of these diverse and numerous sources, which, until now, have been underestimated or scarcely considered. The last historical-educational research perspectives show us that we are in a thriving period in which research into the history of school practices is probing new resources and it is revising the contributions that all resources can offer, testing new processes for review and revision, combining various sources to analyze particular topics, and formulate more holistic interpretative models.